The shadow of fear: hate crime victimization and stress after Charlottesville - Hellyer, Joshua; Gereke, Johanna (Frontiers in Psychology, 2024)
Introduction Recent years have witnessed an increase in highly publicized attacks targeting members of ethnoracial and religious minority groups. To date, existing research has primarily focused on the tendency for such “trigger events” to generate violent aftershocks. We argue that beyond such ripple effects, highly salient trigger events significantly increase hate-crime related stress among racial and ethnic minorities. Additionally, we explore whether these effects are limited to the group most clearly targeted, or if they “spill over” to other minoritized communities. Methods To study reactions to hate crimes, we draw upon national survey data (N = 1,122) in combination with a natural experiment involving the Unite the Right rally and vehicle attack in Charlottesville, Virginia in August 2017. We employ an “unexpected event during survey” design to estimate the causal effect of the Charlottesville rally on stress about hate crimes. Results We first show that there was an increase in anti-Black hate crimes in the 2 weeks following the Charlottesville incident. We also find a corresponding increase in stress due to the perception of personal vulnerability to hate crimes among African-Americans. However, we do not observe a significant increase in levels of stress following the trigger event among Hispanics and Asian Americans. Discussion Our results suggest that highly publicized instances of intergroup violence can have significant impacts on stress about hate crime victimization within the target group. However, we find that this effect is short-lived, and that both violent aftershocks and the general climate of fear spurred by hate crimes may be racially bounded.